Smart devices, applications, and protocols for the IoT - Rodrigues, Joel Jose P. C.; Gawanmeh, Amjad 1975-; Kashif; Parvin, Sazia (IGI Global, 2019)
"This book examines how the new paradigms and tremendous advances in computing, communications and control have provided and supported wide range of applications in all domains of live, in particular, bridging the physical components and the cyber space leading to the smart Internet of Things (IoT)"--
Description based on title screen (IGI Global, viewed 04/06/2019)
Keywords: Internet of things; Intelligent control systems; Computer network protocols